THE JADASSOHN NEVUS IN A NEWBORN: A CASE STUDY FROM NORTH MACEDONIA - Vejseli, Besim Murat; Naunova, Silvana Timovska; Mandzukova, Hristina; Kimovska, Mica; Voinovska, Tamara; Neskova, Spasija; Sofijanova, Aspazija (Journal of Morphological Sciences, 2024)
Jadassohn sebaceous nevus is a rare, benign, congenital skin tumor that belongs to the group of hamartomas. This deformity is manifested by a plaque appearing as a single yellow-orange plaque. Circumscribed alopecia is observed before puberty. A papillomatous transformation can be seen after puberty. Due to the high potential for malignant degeneration, prophylactic surgical removal is very important in childhood. We report the case of a newborn boy presenting with a plaque in the right temporo-parietal region that was present from birth and gave rise to a brownish papular lesion. Keywords: Jadassohn sebaceous nevus, papillomatous transformation, newborn.